THE EFFECT OF GOOD CORPORATE GOVERNANCE AND TAX PLANNING ON COMPANY VALUE - Angga Hidayat; Nike Yuliah (EAJ (Economic and Accounting Journal), 2018)
This study aims to analyze the influence of Good Corporate Governance and tax planning on corporate value. This research is a type of quantitative research. The type of data used is secondary data obtained from www.idx.co.id and the company's website. The analytical method used is multiple regression analysis using SPSS version 22 software. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the period 2013-2017. While the sample of this study was determined by purposive sampling method to obtain a total of 105 data that could be processed.Based on the results of good corporate governance regression analysis which is represented by institusional ownership proxy has a significant effect on firm value and tax planning has a significant effect on firm value.